Case Report: Sustained Efficacy of Lumasiran at 18 Months in Primary Hyperoxaluria Type 1 - Chiodini, Benedetta; Tram, Nathalie; Adams, Brigitte; Hennaut, Elise; Lolin, Ksenija; Ismaili, Khalid (Frontiers in Pediatrics, 2022)
Abstract Background Primary hyperoxaluria type 1 (PH1) is a rare genetic disease caused by hepatic overproduction of oxalate, ultimately responsible for kidney stones, kidney failure and systemic oxalosis. Lumasiran, is a liver-directed RNA interference therapeutic agent. It has been shown to reduce hepatic oxalate production by targeting glycolate oxidase, and to dramatically reduce oxalate excretion. Care report We present the case of a teenager patient affected with by PH1, who entered in the lumasiran compassionate use program. The patient had a rapid and sustained decrease in urinary oxalate/creatinine ratio, with a mean reduction after lumasiran administration of about 70%. During the 18 months long follow-up, urinary oxalate remained low, reaching nearly normal values. Plasma oxalate also decreased dramatically., normal Normal levels were reached immediately after the first dose and remained consistently low thereafter. During the same follow-up period, eGFR remained stable at about 60 ml/min/1.73 m2, but no new kidney stones were observed, and t. Existing kidney stones he existing ones did not increase in size. The child patient did not suffer renal colic events and did not require new further urological interventions. Conclusion In our severely affected PH1 patient, lumasiran proved to be very effective in rapidly and consistently abating reducing plasma oxalate and urinary excretion to normal and near-normal levels respectively. In the 18 months long follow-up post-lumasiran, the eGFR remained stable and the patient showed clinical improvements. As far as we know, this report covers the longest observation period after initiation of this novel RNAi therapy.